1998
DOI: 10.1007/s001980050098
|View full text |Cite
|
Sign up to set email alerts
|

Public Perceptions and Self-Reported Prevalence of Osteoporosis in South Australia

Abstract: The self-reported prevalence of, and attitudes to and perceptions of, osteoporosis in the South Australian community were assessed using data collected as part of the 1995 South Australian Health Omnibus Survey (household interviews)--a clustered, self-weighting, multistage sample of households in metropolitan and country centers. The self-reported prevalence was 4.8 (95% CI: 3.7-5.8) and 1.4% (95% CI: 0.8-2.0) for women (n = 1531) and men (n = 1485) respectively. For individuals with osteoporosis, calcium was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 13 publications
4
18
0
1
Order By: Relevance
“…Osteoporosis is a common disease but often unknown to patients, including those at risk [25], as confirmed by the results of our questionnaire on the degree of patient awareness. Prior to enrolment in our program, 73% of patients believed that their fracture was unrelated to bone fragility.…”
Section: Discussionmentioning
confidence: 63%
“…Osteoporosis is a common disease but often unknown to patients, including those at risk [25], as confirmed by the results of our questionnaire on the degree of patient awareness. Prior to enrolment in our program, 73% of patients believed that their fracture was unrelated to bone fragility.…”
Section: Discussionmentioning
confidence: 63%
“…Although, these findings are contrary to those expected, they do concur with previous studies where perception alone did not dictate protective behaviours. Phillipov et al found in a cross-sectional study that Australian women who had a high risk perception to osteoporosis were 1.6 times less likely to adapt any preventative action towards osteoporosis [38], while Chang et al found that despite 54% of women believing that they were at risk for osteoporosis, 64% of these women perceived barriers to taking actions to reduce this risk [39]. …”
Section: Discussionmentioning
confidence: 99%
“…6 Interestingly, however, even 18% is a high self-reported figure, when compared to a 1995 South Australian Health Survey, which showed a selfreported osteoporosis prevalence of 4.8% and 1.4% for women and men, respectively. 7 This vast difference could be somewhat biased in our population, because the patients have been under medical care for musculoskeletal complaints and thus are perhaps better informed regarding osteoporosis. Our study showed that only 37% of patients with self-reported osteoporosis reported current treatment with bisphosphonates.…”
Section: Discussionmentioning
confidence: 99%